Prof. Alexey V. Konarev (celebrating the 75th birthday) - T. V. Shelenga; Yu. A. Kerv; I. N. Perchuk; V. S. Popov; A. E. Solovyeva; V. I. Khoreva; E. K. Khlestkina (Труды по прикладной ботанике, генетике и селекции)
On January 16, 2023 we celebrated the 75th birthday of Professor Alexey V. Konarev, Doctor of Biological Sciences, a renowned scientist in the sphere of plant biochemistry and molecular biology, one of the eldest staff members of VIR.